Space Tourism: the Emerging Industry of the World Economy - E. A. Efimova (Мир новой экономики, 2024)
Relevance of the research topic: currently, space is considered as a new economic resource, the use of which can generate profit for companies that have access to it. The participation of private capital in space exploration contributes to the search for new business niches and the formation of new economic sectors, one of which is space tourism.   The purpose of the article is to study the current state and development trends of a new branch of the world economy — space tourism.   To conduct the study, general scientific methods were used: analysis, synthesis, deduction, comparative analysis, generalization, as well as special scientific methods: structural analysis, statistical method, grouping method, graphical method and SWOT analysis method. A review of scientific publications on the problems of space tourism development allowed the author to propose his own definition of this phenomenon and identify its main features at the present stage of development. The author identified and analysed the main types of space tourism (orbital, suborbital, lunar and stratospheric), identified the main participants in the global space tourism market, conducted a comparative analysis of the technologies used to provide services for sending tourists into space, and conducted a SWOT analysis of the development of the global space tourism industry, he also analyzed the state of space tourism in Russia. The results and conclusions of the article are of interest to researchers studying the development of economic sectors related to space activities, as well as to government agencies whose decisions affect the development of the space industry in Russia.